Dynamic reciprocity and wound healing - Herman, Ira M. (Henry Stewart Talks, 2014)
Influences of the wound micro-environment to either foster and sustain wound healing or impede wound closure, Matrix-associated signals govern tissue responses, The Dynamic reciprocity paradigm to encompass the ongoing 'crosstalk' between cells and their extracellular milieu in response to injury and during healing, Examples of dynamic reciprocity during wound healing